The Effect of Motivation and Self-Concept on Mathematics Learning Outcomes Senior High School Students - A Rasul; Pandu Adi Cakranegara; Yunus Shobrun; Rendi Hadian Tamagola ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2022)
High mathematics learning outcomes become a benchmark for student success in learning mathematics. Students need self-concept and motivation to achieve high mathematics learning outcomes. This study aims to determine how much self-concept and motivation influence the learning outcomes of Senior High School students. This type of research is ex-post facto research. The population in this study were one of school in Mimika. The number of samples collected using cluster random sampling were 355 students. Data collection techniques used self-concept questionnaires, motivation questionnaires and mathematics learning outcomes tests. The research data were analyzed by descriptive analysis and multiple linear regression analysis. The results showed that: (1) The mathematics motivation of students were categorized as very high, (2) Students' mathematical self-concept were categorized as very high, (3) the mathematics learning outcomes of students were categorized as very high, (4) motivation has a positive effect on mathematics learning outcomes for students, (5) self-concept has a positive effect on mathematics learning outcomes for students, (6) motivation and self-concept have a positive effect on mathematics learning outcomes. Based on the results, we conclude that there is no influence of self-concept and motivation on students' mathematics learning outcomes.